2010
DOI: 10.1598/rrq.45.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Web‐Based Tutoring of the Structure Strategy With or Without Elaborated Feedback or Choice for Fifth‐ and Seventh‐Grade Readers

Abstract: This study investigated the effects of different versions of Web‐based instruction focused on text structure on fifth‐ and seventh‐grade students' reading comprehension. Stratified random assignment was employed in a two‐factor experiment embedded within a pretest and multiple posttests design (immediate and four‐month delayed posttests). The two factors were type of feedback provided by the Web‐based tutor (elaborated vs. simple feedback) and the motivational factor of choice of text topics in practice lesson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 41 publications
5
102
1
Order By: Relevance
“…Based on one-way ANCOVA results, the participants who received immediate detailed feedback scored higher on the energy knowledge posttest than did those who received no IEF. The findings of the study were consistent with previous studies that suggested immediate feedback and elaborated feedback enhanced learning (Corbett & Anderson, 1989;Dihoff, Brosvic, Epstein, & Cook, 2003;Meyer et al, 2010;Van et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Based on one-way ANCOVA results, the participants who received immediate detailed feedback scored higher on the energy knowledge posttest than did those who received no IEF. The findings of the study were consistent with previous studies that suggested immediate feedback and elaborated feedback enhanced learning (Corbett & Anderson, 1989;Dihoff, Brosvic, Epstein, & Cook, 2003;Meyer et al, 2010;Van et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Since there is some evidence for the efficacy of anthropomorphic characters with spoken, as opposed to written, feedback (e.g., Heidig & Clarebout, 2011;Lusk & Atkinson, 2007), the PA in the current study was designed as an animated, speaking mouse with anthropomorphic features in appearance and speech. Unlike digital reading tutors in other programs, the PA in the current study did not teach specific strategies such as self-questioning or identification of main ideas, followed by elaborate feedback, as students tried to apply the learned strategy (e.g., Meyer et al, 2010;Mich, Pianta, & Mana, 2013;Sung, Chang, & Huang, 2008). Unlike other reading support systems such as Meyer et al (2010), who provided explicit instruction on how to identify and use text structures, or Sung et al (2008) who instructed students about concept mapping and highlighting important messages, the current study did not provide explicit instruction on reading strategies.…”
Section: Guidance During Readingmentioning
confidence: 99%
“…Meyer et al [12] compared the effects of a web-based tutoring system on different measures of reading comprehension. The participants were 111 grade 5 and 7 students.…”
Section: Technology and Softwarementioning
confidence: 99%